Biotechnological risks of obtaining amyloglucosidase under conditions of altered gravity - Rymarchuk, A.O.; Andrianova, T.V. (Problems of Environmental Biotechnology, 2023)
The risks of biotechnologies for producing amyloglucosidase under altered gravity are considered.